Assessing the implications of the recent community opening policy on the street centrality in China: A GIS-based method and case study. (December 2017) - Yu, Wenhao
Abstract: Recently, the Chinese government raised an urban planning policy which suggests communities open their private roads for public transport and establish street networks with high spatial density in cities. In this context, the purpose of this study is to analyze the potential changes to street network accessibility using GIS techniques and to provide spatial information that may influence the decision making of urban managers. In addition to the existing street network data in the case study city, Shenzhen, intra-community roads are extracted from building footprints in GIS topographic database and used to construct a potential street network with respect to the community opening policy. An automatic GIS-based method is proposed here to analyze the location advantage information in the simulated urban environment, by combining Delaunay triangulation model and graph theory concepts. Specifically, we establish a two-step framework based on the spatial relationships between roads and buildings. Firstly, intra-community roads between neighboring building footprints are generated using a Delaunay triangulation skeleton model, and with the existing inter-community roads they form the simulated network. Secondly, street centrality indices of the current and simulated networks are compared in terms of closeness, betweenness and straightness. Results indicate that after applying the policy the global accessibility in the city would be increased at some places and decreased at others, and places' directness among others would be generally improved. In addition, the skeleton of central routes for through traffic would not change much. The presented method can also be applied to other cities. Highlights: Delaunay triangulation-based model was developed for generating intra-community road central lines. A new method was developed for predicting urban accessibility changes under the Community Opening policy. A policy suggestion was provided through a case study in China.